The empire of the artistic: creation and consumption in the age of transaesthetic capitalism. [DOI:10.37785/nw.v5n1.a9] - Rivera, Eduardo Correa (Nawi, 2021)
The current phase of our global economic system has encouraged the need to encase our daily practices and consumption with symbolic values. To that end, it has extracted a series of operations from the institutional artistic system and has deployed them through different forms of material and affective culture, making our world a fully aestheticized scene, anxious of the artistic experience as the background of all its habits and ways of relationship. That process has revived the concept of genius, this time as a registered trademark, as a designer or as a digital content creator. However, this does not imply a decline in artistic production based on a superficial addition. This new horizon is also an opportunity to extend the possibility of creation through the appropriation of tools and circuits of common access.